Disleksia dalam konteks pembelajaran bahasa di Malaysia - Subramaniam, Vijayaletchumy (Universiti Putra Malaysia Press, 2008)
The purpose of this paper is to inform the public about dyslexia in the context of learning of language in Malaysia. The researcher had conducted a survey on 7 subjects in Sekolah Kebangsaan Serdang. The research instruments were Jordan Writing Screening Test (JWST) and Jordan Oral Screening Test (JOST). The outcome of this research shows that there are two types of dyslexia in the reading aspect of Malay Language; visual dyslexia and auditory dyslexia. The outcome of this research also indicated dyslexic student ability to read and to learn language.